Post-Translational Modifications in Oocyte Maturation and Embryo Development - Wu, Yu; Li, Mo; Yang, Mo (Frontiers in Cell and Developmental Biology, 2021)
Mammalian oocyte maturation and embryo development are unique biological processes regulated by various modifications. Since de novo mRNA transcription is absent during oocyte meiosis, protein-level regulation, especially post-translational modification (PTM), is crucial. It is known that PTM plays key roles in diverse cellular events such as DNA damage response, chromosome condensation, and cytoskeletal organization during oocyte maturation and embryo development. However, most previous reviews on PTM in oocytes and embryos have only focused on studies of Xenopus laevis or Caenorhabditis elegans eggs. In this review, we will discuss the latest discoveries regarding PTM in mammalian oocytes maturation and embryo development, focusing on phosphorylation, ubiquitination, SUMOylation and Poly(ADP-ribosyl)ation (PARylation). Phosphorylation functions in chromosome condensation and spindle alignment by regulating histone H3, mitogen-activated protein kinases, and some other pathways during mammalian oocyte maturation. Ubiquitination is a three-step enzymatic cascade that facilitates the degradation of proteins, and numerous E3 ubiquitin ligases are involved in modifying substrates and thus regulating oocyte maturation, oocyte-sperm binding, and early embryo development. Through the reversible addition and removal of SUMO (small ubiquitin-related modifier) on lysine residues, SUMOylation affects the cell cycle and DNA damage response in oocytes. As an emerging PTM, PARlation has been shown to not only participate in DNA damage repair, but also mediate asymmetric division of oocyte meiosis. Each of these PTMs and external environments is versatile and contributes to distinct phases during oocyte maturation and embryo development.